IMPROVING STUDENTS SPELLING ABILITY BY USING MAKING WORDS IN SDN 6 PALEMBANG - Wahyudi Agus; Pamuji Arief (JAMBI-ENGLISH LANGUAGE TEACHING, 2016)
Spelling is the forming of words from written and oral forms according to accepted usage. English spelling is difficult and often unpredictable. To be a better speller, a student must be able to remember sounds of letters in isolation as well as how to blend them into whole words. The students need a great deal or practice using the words functionally, as in writing. Therefore, the students have to associate letter sounds with the correct letters. Making Words is an innovative word study and word play activity, students are guided through the process of using a limited number of letters to make a series of words. This study was conducted in SD Negeri 6 Palembang, One of the quasi-experimental designs, the pretest-posttest non-equivalent control group design was applied in this study. The results of the study showed that there was significant difference in Spelling ability between the students who were taught by using Making Words and those who were not. On the basis of the independent samples test, t-obtained of the posttest of experimental and control groups was 2.511. Finally, the results of the interview showed that most of the students were interested in learning Spelling through Making Words. Therefore, Making Words is an effective way to be used in teaching spelling. Keywords:  Spelling, Making Words, Young Learners